2020
DOI: 10.1167/iovs.61.10.17
|View full text |Cite
|
Sign up to set email alerts
|

BBSome Component BBS5 Is Required for Cone Photoreceptor Protein Trafficking and Outer Segment Maintenance

Abstract: To identify the role of the BBSome protein Bardet-Biedl syndrome 5 (BBS5) in photoreceptor function, protein trafficking, and structure using a congenital mutant mouse model. METHODS. Bbs5-/mice (2 and 9 months old) were used to assess retinal function and morphology. Hematoxylin and eosin staining of retinal sections was performed to visualize histology. Electroretinography was used to analyze rod and cone photoreceptor function. Retinal protein localization was visualized using immunofluorescence (IF) within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…It has previously been reported that male Nphp4 -/mice are sterile due to sperm motility defects (WON et al 2011). Similarly, we previously described sterility defects and sub-mendelian ratios at birth and weaning in congenital Bbs5 -/animals (BALES et al 2020;BENTLEY-FORD et al 2021). For this reason, double heterozygous Bbs5 -/+ ;Nphp4 -/+ female by Bbs5 -/+ ;Nphp4 -/+ male matings were established.…”
Section: Bbs-5 and Nphp-4 Are Individually Necessary For Transition Zone Integritymentioning
confidence: 75%
“…It has previously been reported that male Nphp4 -/mice are sterile due to sperm motility defects (WON et al 2011). Similarly, we previously described sterility defects and sub-mendelian ratios at birth and weaning in congenital Bbs5 -/animals (BALES et al 2020;BENTLEY-FORD et al 2021). For this reason, double heterozygous Bbs5 -/+ ;Nphp4 -/+ female by Bbs5 -/+ ;Nphp4 -/+ male matings were established.…”
Section: Bbs-5 and Nphp-4 Are Individually Necessary For Transition Zone Integritymentioning
confidence: 75%
“…However, mutations of core human BBSome components will not cause early mortality. This is also supported by mouse models, which showed that no embryonic lethality was found in the homozygous mutant mice when BBSome genes were disrupted globally (Bales et al, 2020; Mykytyn et al, 2004; Q. Zhang et al, 2011, 2013). Spermatogenesis was affected in these global knockout mice, but it is not known which cells contributed to the failure of sperm formation.…”
mentioning
confidence: 80%
“…To further investigate the role of the BBSome in photoreceptor function, we turned to the zebrafish, an established animal model for ciliopathies [42][43][44] . The cone-rich retina of zebrafish larvae represents a particular asset to study this photoreceptor subtype compared to the rod-dominated mouse retina, as diverging effects on cone and rod photoreceptors have been described 38,41,45 . In this work, we generated a new zebrafish bbs1 knock-out model and found that despite normal retinal development and photoreceptor differentiation, visual functional deficits were present prior to the appearance of any morphological anomaly in mutant fish.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous BBSome mutant studies highlight the crucial role of the BBSome complex for photoreceptor homeostasis and morphogenesis 40,41,45 . The bbs1 mutant zebrafish presented here recapitulates the progressive retinal dysfunction and degeneration seen in humans and in all published models.…”
Section: Discussionmentioning
confidence: 99%